2014
DOI: 10.3390/molecules19033820
|View full text |Cite
|
Sign up to set email alerts
|

Goat Milk Fat Naturally Enriched with Conjugated Linoleic Acid Increased Lipoproteins and Reduced Triacylglycerol in Rats

Abstract: Goat milk is source of different lipids, including conjugated linoleic acid (CLA). CLA reduces body fat and protect against cardiovascular diseases. In the present study fat from goat milk naturally enriched with CLA was used. Male Wistar rats were divided into three groups that received during a 10 week diet with different lipid sources: soybean oil (CON), coconut oil (CO) and goat milk fat naturally enriched with CLA (GM-CLA). We evaluated the effects of a GM-CLA on biochemistry parameters -high density lipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 50 publications
0
6
0
1
Order By: Relevance
“…The obtained results did not reveal significant effects on body weight. Similar studies, based on rats, were performed by Rodrigues et al [109], who examined the influence of goat milk fat naturally enriched with CLA. Similarly to the previous study, body weight of the examined rats in comparison to control group was not much lower.…”
Section: Conjugated Fatty Acidsmentioning
confidence: 64%
“…The obtained results did not reveal significant effects on body weight. Similar studies, based on rats, were performed by Rodrigues et al [109], who examined the influence of goat milk fat naturally enriched with CLA. Similarly to the previous study, body weight of the examined rats in comparison to control group was not much lower.…”
Section: Conjugated Fatty Acidsmentioning
confidence: 64%
“…The CLA improved insulin resistance by increasing mRNA expression of PPAR-γ, and its target genes such as fatty acid binding proteins, fatty acid transporter proteins and adiponectin in the adipose tissues of the obese rats. In another study, Rodrigues et al (2014) used fat from goat milk naturally enriched with CLA to investigate the effects of CLA on serum lipids and glucose, body weight, and intestinal and liver histopathological parameters of male rats. They showed that CLA caused an increase in the body weight of the rats from the second to the fifth wk of the experiment, indicating its growth promoting activity in young rats.…”
Section: Effects Of Cla On Cancermentioning
confidence: 99%
“…A westernized diet increases the bacteria counts belonging to phylum Firmicutes which are associated with negative impacts on human health [40]. However, our results show that GMW supplementation increases the number of total lactobacilli in both dams and offspring.…”
Section: Journal Of Food and Nutrition Researchmentioning
confidence: 49%